2007
DOI: 10.1017/s0022050707000411
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Interpretation of the Constitutional Convention of 1787 Revisited

Abstract: Empirical studies of delegate voting at the Constitutional Convention have relied on the same 16 roll call votes. This article re-examines various assumptions used in the collection of these data. We first create a baseline regression. We then consider the effect of dropping delegates not in attendance, re-inferring the votes from primary sources, examining various subsamples of the roll calls, and reconstructing constituency variables to include state districts. Our findings suggest that personal interests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
1
16
2
Order By: Relevance
“…Rather, our estimates suggest that on the key votes related to money and debt issues delegates were indeed influenced by their own personal economic considerations. These findings are consistent with many of the conclusions reached by McGuire and Ohsfeldt (1986, 1997), McGuire (2003, and Heckelman and Dougherty (2007) who analyzed the same set of 16 disparate clauses. Furthermore, the lack of significant state characteristics in our regression analysis supports Heckelman and Dougherty's (2007) finding that state constituency interests may have been less important than previously claimed Ohsfeldt 1986, 1997;McGuire 2003).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Rather, our estimates suggest that on the key votes related to money and debt issues delegates were indeed influenced by their own personal economic considerations. These findings are consistent with many of the conclusions reached by McGuire and Ohsfeldt (1986, 1997), McGuire (2003, and Heckelman and Dougherty (2007) who analyzed the same set of 16 disparate clauses. Furthermore, the lack of significant state characteristics in our regression analysis supports Heckelman and Dougherty's (2007) finding that state constituency interests may have been less important than previously claimed Ohsfeldt 1986, 1997;McGuire 2003).…”
Section: Introductionsupporting
confidence: 89%
“…They also imputed the votes of delegates not in attendance using additional assumptions. As shown by Heckelman and Dougherty (2007), both McDonald's initial inferences and McGuire and Ohsfeldt's additional imputations may have biased the results in favor of state factors and away from personal delegate factors. By limiting the sample to actual voters, and making new inferences on the original data, Heckelman and Dougherty (2007) found that the importance of delegate economic interests increased and the importance of state interests decreased.…”
Section: Critics and Supportersmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that both personal economic interests and constituent interests affected delegate voting behavior at the margin. Heckelman and Dougherty (2007) presented a detailed critique of the inferences made by McDonald (1958) and Ohsfeldt (1986, 1997), re-inferred the same 16 votes using primary source data, and concluded that personal interests were more important than constituent interests. Although these more recent studies represent the most advanced empirical work on the motivation of the delegates at the Constitutional Convention, they do not include any issues related to slavery.…”
Section: Motivation Of the Framersmentioning
confidence: 99%
“…Thus, there is good reason to expect strategic "talking" to be rare. Our inference of delegate level votes proceeded in three basic steps, similar to the steps outlined by Heckelman and Dougherty (2007). We implement a fourth step in the Appendix to obtain additional observations used in supplemental regressions.…”
mentioning
confidence: 99%